AN EXPLORATION OF THE INDIGENOUS SCIENCE OF NGERUPUK LOCAL CULTURE IN PETANG INDIGENOUS VILLAGE AND ITS RELEVANCE TO SCIENCE - I Gusti Ayu Mutiara Sandhy; Kompyang Selamet; luh Mitha Priyanka (Jurnal IPA Terpadu, 2024)
This research aims to explore the indigenous science of the Ngerupuk tradition as local culture in the Petang Traditional Village and analyze its relevance to junior high school science materials. This type of research is descriptive qualitative, with an ethnoscience approach. The research was conducted in the Petang Traditional Village, Badung. Through purposive sampling and snowball sampling techniques, a total of 6 research subjects were obtained, including the Community component consisting of stakeholders, Serati Banten, community leaders, and science teachers at SMP Negeri 1 Petang. Data collection techniques were carried out using observation, interviews, documentation and questionnaires. The data analysis technique uses Milles and Huberman which consists of collecting data, reduction, data display, and conclusion. The results are a number of indigenous knowledge of the community about the Siat Api ritual or fire war and Mecaru panca sata which is the main activity of the Ngerupuk tradition of the Evening Traditional Village. Based on scientific analysis, it was found that the findings are relevant and have a great opportunity to be studied in Phase D Middle School Science, namely in the material of classifying living things, heat and movement, organization of life, air pollution, vibrations, waves and sound.